From graphene to graphene oxide: the importance of extended topological defects. Issue 4 (11th January 2022) - Marsden, Alexander J.; Skilbeck, Mark; Healey, Matthew; Thomas, Helen R.; Walker, Marc; Edwards, Rachel S.; Garcia, Natalya A.; Vuković, Filip; Jabraoui, Hicham; Walsh, Tiffany R.; Rourke, Jonathan P.; Wilson, Neil R.
Abstract : By microscopy, spectroscopy, and modelling we show that extended topological defects are ubiquitous in oxygen functionalised graphene, whether from gas-phase or wet-chemical oxidation, and play a critical role in limiting its reduction and stiffness. Abstract : Graphene oxide (GO) represents a complex family of materials related to graphene: easy to produce in large quantities, easy to process, and convenient to use as a basis for further functionalization, with the potential for wide-ranging applications such as in nanocomposites, electronic inks, biosensors and more. Despite their importance, the key structural traits of GO, and the impact of these traits on properties, are still poorly understood due to the inherently berthollide character of GO which complicates the establishment of clear structure/property relationships. Widely accepted structural models of GO frequently neglect the presence of extended topological defects, structural changes to the graphene basal plane that are not removed by reduction methods. Here, a combination of experimental approaches and molecular simulations demonstrate that extended topological defects are a common feature across GO and that the presence of these defects strongly influences the properties of GO. We show that these extended topological defects are produced following even controlled 'gentle' functionalization by atomic oxygen and are comparable to those obtained by a conventional modified Hummers' method. The presence of the extended topological defects is shown to play an important role in the retention of oxygen functional groups after reduction. As an exemplar of their effect on the physical properties, we show that the GO sheets display a dramatic decrease in strength and stiffness relative to graphene and, due to the presence of extended structural defects, no improvement is seen in the mechanical properties after reduction. These findings indicate the importance of extended topological defects to the structure and properties of functionalized graphene, which merits their inclusion as a key trait in simple structural models of GO.